Technical Performance for Heat Storage of Solar Cooker using Vegetable Oil as Working Fluid - Prompuge, Wittaya; Sirisamphanwong, Chatchai (Journal of Renewable Energy and Smart Grid Technology, 2018)
The purposes of the study are to design the solar cooker which used vegetable oil as a heat transfer medium. From the technical performance for heat storage of solar cooker using vegetable oil as working fluid, equipped with evacuating tube of collector an absorber-plate, the palm oils acting as fluid for heat. The design of the system allows its benefits of fixed position on during all of the year. The various foods test the real climatic conditions of Phitsanulok, Thailand showing the solar cookers effectiveness to cook two meals per day. Condition during the cooker works on flow rate of palm oil per day was 0.0025 kg/s and specific heat capacity of palm oil was 2.19 kJ/kg °C, the collector area was 0.78 m2 and given average of solar radiation per day were 668.43 W/m2. The maximum and minimum temperature of vessel was 95.94 °C and 57.82 °C respectively that enable to boiled water up to 86 °C, efficiency was at 40.06%. This system can be applied to a kitchen wall of a building. It could be then made use for no sunshine. The result of experiment showed that the solar cooker in this study is usable, there are some factor which can increase its heat efficiency. A solar cooker is used in summer with high temperature and high solar radiation, there is increased and quick heat capacity produced by the solar cooker.